Aryl borane as a catalyst for dehydrative amide synthesis - Gavit, Amit Vinayak; Talekar, Sanjana S.; Mane, Manoj V.; Sawant, Dinesh Nanaji (Journal of Organic Chemistry, 2025)
Tris(pentafluorophenyl)borane B(C6F5)(3)H2O is reported as a catalyst for dehydrative amidation of carboxylic acids and amines. This protocol is applicable across a wide range of >35 substrates, including aromatic and aliphatic amines and acids, resulting in amides in <= 92% yields. The scalability of the reaction up to 10 mmol, along with the synthesis of drugs such as ibuprofen amide, moclobemide, and phenacetin, demonstrates the industrial potential of our protocol.